(untitled) - Muhammad Amir; Dr. Saeedur Rehman; Dr. Syed Rashid Ali (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2023)
The state of Swat was an organized government in the Pakhtun regions of Pakistan. The rulers of Swat state were educated, experienced and loved the citizens of the state. This state was merged into Pakistan in 1969. The judicial affairs of this state were very simple and mirrored the traditions, civilization and religion of the local Pakhtun population. Swat Nama was the constitutional document of the Swat state which was agreed upon by the entire Pakhtun nation. "Riwaj Nama e Swat" of the State of Swat contains a large number of decrees in which criminal, civil and other types of decrees are recorded in a detailed manner. In this article a shari’a and research review of honor killing among civil powers has been done regarding the order of the same "Riwaj Nama e Swat". This paper is divided into two main topics. In the first part, the introduction and background of "Riwaj Nama e Swat" is described, while in the second part, various cases of honor killings are explained in the light of "Riwaj Nama e Swat". At the end of the paper, the summary discussion, recommendations and references are listed in the form of endnotes.